New Species for the Fauna of Turkey with description of genitalia of Acrobasis farsella Amsel, 1950 (Lepidoptera: Pyraloidea) - K. Akin; E. Seven (SHILAP)
Agriphila cyrenaicella Ragonot, 1887 and Acrobasis farsella Amsel, 1950 are new records for the Pyraloidea fauna of Turkey. While the male genitalia of A. farsella are redescribed, the female genitalia are described for the first time. Besides, figures of the species are presented in the study.